Geographic isolation and technological change: A new vision of teaching and learning in rural schools in New Zealand - Ken Stevens (Flexible Learning Association of New Zealand, 2012)
Some small rural schools in New Zealand are currently developing new ways of applying information and communication technologies to the delivery of education while, at the same time, struggling to justify their continued existence. The development of teaching and learning networks in rural New Zealand enables resources to be shared and educational opportunities for those who live in geographically isolated parts of the country to be increased. It is further argued that, because of these developments, it is now appropriate to reconsider the significance of the size and the location of learning institutions, the ways in which education is delivered and the meaning of large and small schools.